Potret Perempuan Dalam Lirik Lagu - Netty Dyah Kurniasari (Jurnal Komunikasi, 2009)
Song Indonesia condition majority with love [relation/link] depicting gender construction in society Song lyric ' Gaya' representing effort for the deconstruction of gender construction which usually predominate Indonesia song majority. Target of this research to find construction idea [of? composer ( Azis, MS about gender relationship which [is] represented in song lyric ' Gaya. Besides also to depict how gender relationship in song lyric ' Gaya '.Methodologies weared [by] research qualitative having a purpose analytical and systematic. Technique analyse and data interpretation which [is] used in this research use framework frorn conducive M.A. K Halliday and approach analyse critical discourse property of Sara Mills. Pursuant to M.A.K Halliday framework got to be to be found that composer construction wish to submit the following message: that [do] not only just men which can affairs but woman also can; woman depicted [by] [is] with its type humanity; that lesbian have to be accepted as [by] an existing in society; and also depiction [of] woman buttonhole which dare to affair. In a flash, Azis [do/conduct] deconstruction role [of] existing gender in society. But, after analysed to wear Sara Mills framework got [by] conclusion that gender relationship which there are in song lyric Gaya' [is] woman which [is] affairs assumed below par and digress. this Song lyric nor give 'place' to attendance [of] lesbian clan.Pursuant to result of interview, please find that Azis intention lift lesbian theme, gender deconstruction values and coitus in Style song so that its song [is] taken a fancy to, to be assumed saleable and bizzare [in] market ( capitalism orientation).